PELAKSANAAN PEMBAGIAN WARIS ADAT MINANGKABAU DI NAGARI BIARO GADANG KECAMATAN AMPEK ANGKEK KABUPATEN AGAM PROPINSI SUMATERA BARAT - Thannisa Dwi Syafitri; Firdaus '; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Indonesian society is a pluralistic society, because Indonesian people themselves made up of various tribes, and each tribe is governed by the law of their customs. This occurs also in the law of inheritance that has diversity, one of which is applied to the area of inheritance West Sumatra embrace traditional Minangkabau. Treasure pusako in minangkabau pusako property is two high and low pusako treasure. In general, treasure pusako reduced in accordance with the lineage of women and high pusako property can not be divided or sold. But there is one village that deviate from customary provisions minang in general in this village there are several high pusako land that has been sold and divided families magnitude adapted to Islamic law. Nagari which adopts a different inheritance of indigenous applied Minang people in general are Nagari Biaro. I researched this research establishes key issues, namely First, What is the procedure customary division of inheritance in Minangkabau in Nagari Biaro Gadang Kecamatan Ampek Angkek Agam District of West Sumatra Province? Second, why there are differences in the division of inheritance in Minangkabau customary in Nagari Biaro Gadang Kecamatan Ampek Angkek Agam District of West Sumatra Province with indigenous Minangkabau in general? The method used in this research from the standpoint of its kind classified into types of research Sociological Empirical namely Research To determine the effectiveness of the Law, while from the point of its nature, this research is descriptive, the intention is to describe the complete and detailed on the Implementation Division of Waris Adat Minangkabau Nagari Biaro Gadang Kecamatan Ampek Angkek Agam District of West Sumatra province. The conclusions in this study is the first, pusako high in villages Biaro Gadang held ownership rights by boys of the descendants of the mother, it is inversely proportional to the provisions actually in indigenous Minangkabau namely pusako height should be collective or can not be divided and proprietary rights held by the daughter of the maternal lineage. Secondly, a difference that occurs is due to the strong influence of Islam and which local indigenous communities are predominantly Islamic, other factors also due to the protests of the sons of the people that are judging the division of inheritance customs was unfair, and the extinction of offspring women who sasuku saparuik and sapayuang. Keywords: Customary Law - Inheritance Law – Minangkabau Custom - Distribution of Inheritance